An inadvertent issue of human retina exposure to endocrine disrupting chemicals: A safety assessment. (February 2021) - Li, Minghui; Yang, Tian; Gao, Lixiong; Xu, Haiwei
Abstract: Endocrine disrupting chemicals (EDCs) are a group of chemical compounds that present a considerable public health problem due to their pervasiveness and associations with chronic diseases. EDCs can interrupt the endocrine system and interfere with hormone homeostasis, leading to abnormalities in human physiology. Much attention has been focused on the adverse effects EDCs have on the reproductive system, neurogenesis, neuroendocrine system, and thyroid dysfunction. The eye is usually directly exposed to the surrounding environment; however, the influences of EDCs on the eye have received comparatively little attention. Ocular diseases, such as ocular surface diseases and retinal diseases, have been implicated in hormone deficiency or excess. Epidemiologic studies have shown that EDC exposure not only causes ocular surface disorders, such as dry eye, but also associates with visual deficits and retinopathy. EDCs can pass through the human blood-retinal barrier and enter the neural retina, and can then accumulate in the retina. The retina is an embryologic extension of the central nervous system, and is extremely sensitive and vulnerable to EDCs that could be passed across the placenta during critical periods of retinal development. Subtle alterations in the retinal development process usually result in profound immediate, long-term, and delayed effects late in life. This review, based on extensive literature survey, briefly summarizes the current knowledge about the impact of representative manufactured EDCs on retinal toxicity, including retinal structure alterations and dysfunction. We also highlight the potential mechanism of action of EDCs on the retina, and the predictive retinal models of EDC exposure. Graphical abstract: Image 1 Highlights: EDCs can pass through the placenta and can then accumulate in the retina. EDC exposure associated with visual deficits and retinopathy. EDC exposure caused retinal structure and dysfunction. EDCs exert actions through binding NHRs, biotransformation or disrupting retinoid signaling. Novel in vivo and in vitro testing models applied to test retinal toxicity.